Editorial Note - Ovamir Anjum (American Journal of Islam and Society, 2023)
This issue of the American Journal of Islam and Society comprises four main research articles, each shedding light on the diverse ways in which the Islamic legal and theological tradition has shaped and intersected with premodern and modern societies. To start closer to home: Sam Houston’s contribution entitled “The “Metaphysical Monster” and Muslim Theology: William James, Sherman Jackson, and the Problem of Black Suffering” places American Muslim scholar Sherman A. Jackson’s important monograph Islam and the Problem of Black Suffering in conversation with the work of American pragmatist philosopher William James and suggests that Jackson’s account parallels James’s account of religion in that it speaks of the “practical effectiveness” of the “web of beliefs” constituting Islamic doctrines of God.